PHYSICAL CHANGES OF TILAPIA FISH BURGER DURING FROZEN STORAGE - Bainy, Eduarda M.; Bertan, Larissa C.; Corazza, Marcos L.; Lenzi, Marcelo K. (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2015)
The effects of frozen storage on weight loss during freezing, cooking yield, dimensional changes, and instrumental texture parameters of tilapia fish burger were evaluated during 6 months. Frozen storage for 1 month significantly increased the fish burger shear force, hardness and thickness reduction. Weight loss during freezing (0.6 ± 0.1 %) did not increase with storage time. There was no hardness (29.9 ± 0.7 N) and shear force (5.5 ± 0.2 N) increase during the frozen storage from 1 to 6 months. Tilapia fish burger can be stored for up to 6 months with minor physical changes.